A Retrospective Review of Hospitalized Patients Receiving a Higher than Maximum Dose of Acetaminophen. (February 2023) - Clark, Alexander T.; Miller, Matthew; Minns, Alicia B.; Derry, Katrina; Stevens, Craig; Clark, Richard F.
Background: Although the 3 to 4 gram per 24 hours dose recommended for daily use are generally safe, case reports and some series raise concerns about nonacute excessive doses in some individuals. Objective: To assess the safety of dosing more than 4 grams of acetaminophen in a 24-hour period in hospitalized patients and develop a method to evaluate the ongoing practice of acetaminophen dosing. Methods: We performed a retrospective chart review of supratherapeutic doses of acetaminophen over a 2-year period. Outcomes included death and the need for liver transplant. A "best practices alert" (BPA) was then developed in our EMR when more than 4 grams of acetaminophen was either prescribed or administered in a 24- hour period. Twelve months of alerts were then retrospectively reviewed and evaluated. Results: 152 cases of dosing more than 4 grams were initially identified. No cases of death related to liver failure or liver transplant were found in any of these patients. 482 cases were identified after a BPA was put in place where the alert was overridden. There were no deaths and no cases that required liver transplantation due to liver failure. The majority of overrides were due to the allowed window of timing for nursing administration of acetaminophen for scheduled doses and overlap with as needed dosing. Conclusion: Supratherapeutic dosing of acetaminophen in our patients did not lead to death or liver transplant. A BPA in our EMR has allowed better evaluation of patterns of acetaminophen use at our university health system.